QSR customer sustainable behaviors and brand practice perceptions on willingness to pay a premium. Issue 2 (2nd December 2019) - Ottenbacher, Michael C.; Kuechle, Graciela; Harrington, Robert James; Kim, Woo-Hyuk
Abstract : Purpose: The purpose of this paper is to investigate the effect of consumer sustainability attitudes and quick service restaurants (QSRs) practices along with the willingness of consumers to pay a premium for sustainability efforts. Design/methodology/approach: A random sample of QSR customers in Germany resulted in 428 completed surveys. First, common factor analysis was conducted to assess the summated scales related to the sustainable behavior of customers, the importance attached by them to the different dimensions of sustainability and the extent to which customers perceive that QSR implement such practices. Second, the effect of these summated scales on the willingness to pay a premium (WTPP) for sustainability practices were assessed by means of a logistic regression. Findings: The findings indicated that WTPP for sustainability efforts is primarily driven by internal beliefs and behaviors of consumers themselves rather than actions by QSR firms. Furthermore, when comparing five major QSRs, QSR brands did not appear to create a strong point of differentiation in their sustainability practices in the minds of frequent QSR consumers in the context of this study. Practical implications: Implications of these results suggest that a growing number of consumers place high importance on sustainability and engage in personal sustainability practices that impact behaviors such as QSR selection and a WTPP for QSR brands and products that are perceived as implementing sustainable practices. Originality/value: This paper addresses a gap by assessing drivers of willingness of QSR customers to pay a premium for sustainable practices and if QSR brands sustainability practices differ in the minds of consumers.